Predictors of 30-Day Pulmonary Complications after Video-Assisted Thoracoscopic Surgery Lobectomy - Holleran, Timothy J.; Napolitano, Michael A.; Duggan, John P.; Peters, Alex S.; Amdur, Richard L.; Antevil, Jared L.; Trachiotis, Gregory D. (The Thoracic and Cardiovascular Surgeon, 2022)
Background Pulmonary complications are the most common adverse event after lung resection, yet few large-scale studies have examined pertinent risk factors after video-assisted thoracoscopic surgery (VATS) lobectomy. Veterans, older and less healthy compared with nonveterans, represent a cohort that requires further investigation. Our objective is to determine predictors of pulmonary complications after VATS lobectomy in veterans.Methods A retrospective review was conducted on patients who underwent VATS lobectomy from 2008 to 2018 using the Veterans Affairs Surgical Quality Improvement Program database. Patients were divided into two cohorts based on development of a pulmonary complication within 30 days. Patient characteristics were compared via multivariable analysis to determine clinical predictors associated with pulmonary complication and reported as adjusted odds ratios (aORs) with 95% confidence intervals. Patients with preoperative pneumonia, ventilator dependence, and emergent cases were excluded.Results In 4,216 VATS lobectomy cases, 480 (11.3%) cases had ≥1 pulmonary complication. Preoperative factors independently associated with pulmonary complication included chronic obstructive pulmonary disease (COPD) (aOR = 1.37 [1.12–1.69]; p = 0.003), hyponatremia (aOR = 1.50 [1.06–2.11]; p = 0.021), and dyspnea (aOR = 1.33 [1.06–1.66]; p = 0.013). Unhealthy alcohol consumption was associated with pulmonary complication via univariable analysis (17.1 vs. 13.0%; p = 0.016). Cases with pulmonary complication were associated with increased mortality (12.1 vs. 0.8%; p < 0.001) and longer length of stay (12.0 vs. 6.8 days; p < 0.001).Conclusion This analysis revealed several preoperative factors associated with development of pulmonary complications. It is imperative to optimize pulmonary-specific comorbidities such as COPD or dyspnea prior to VATS lobectomy. However, unhealthy alcohol consumption and hyponatremia were linked with development of pulmonary complication in our analysis and should be addressed prior to VATS lobectomy. Future studies should explore long-term consequences of pulmonary complications.
Keywords: thoracoscopic/VATS; surgery; complications; outcomes (includes mortality, morbidity); database